2018
DOI: 10.1111/eci.12963
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase‐9, 10, and stress hyperglycaemia in acute kidney injury

Abstract: Stress hyperglycaemia is a common condition among nondiabetic geriatric patients with AKI and is related to mortality. Serum MMP-10 levels serve as an important predictor of the necessity of emergency RRT in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…By contrast, Wang et al [ 8 ] reported that among non-diabetic patients with stress hyperglycemia and AKI, glucose levels correlated with urinary N-acetyl-β-D-glucosaminidase (uNAG), which is another marker of tubular injury. Guvercin et al [ 9 ] found that serum matrix metalloproteinase (MMP)-9 levels were associated with the need for dialysis and with mortality among non-diabetic geriatric patients with stress hyperglycemia and AKI. Moriyama et al reported that hyperglycemia upon admission was found to be an independent predictor of AKI among 664 Japanese patients presented with acute myocardial infarction (AMI), a third of them, only, with diabetes [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, Wang et al [ 8 ] reported that among non-diabetic patients with stress hyperglycemia and AKI, glucose levels correlated with urinary N-acetyl-β-D-glucosaminidase (uNAG), which is another marker of tubular injury. Guvercin et al [ 9 ] found that serum matrix metalloproteinase (MMP)-9 levels were associated with the need for dialysis and with mortality among non-diabetic geriatric patients with stress hyperglycemia and AKI. Moriyama et al reported that hyperglycemia upon admission was found to be an independent predictor of AKI among 664 Japanese patients presented with acute myocardial infarction (AMI), a third of them, only, with diabetes [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, hyperglycemia, irrespective to diabetes, may foresee the risk of AKI in patients presented with severe acute illness, as shown, for instance, in patients with COVID-19 disease [ 6 ]. Yet, while the impact of hyperglycemia upon admission on mortality has been thoroughly studied [ 7 ], data are limited regarding renal outcome [ 8 , 9 , 10 ], other than in the setup of acute myocardial infarction and coronary interventions [ 11 , 12 , 13 , 14 ]. Nevertheless, KDIGO guidelines suggest a correction of hyperglycemia among measures aimed at reducing AKI, for example in perioperative settings [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…MMP-10 was reported to be associated with atherosclerosis (Purroy et al , 2018), intracerebral hemorrhage (Howe et al , 2018), pulmonary hypertension (Avouac et al , 2017), and cancers (Miyata et al , 2007; Du et al , 2014; Kadeh et al , 2016; Juchniewicz et al , 2017). Recently, Guvercin et al reported that the increase of serum MMP-10 is related to acute kidney injury in nondiabetic geriatric patients (Guvercin et al , 2018). Our data demonstrated that the expression of MMP-10 in normal kidney tissues is very weak, but could be strongly activated by IRI treatment, supporting that MMP-10 is a potential candidate involved in renal IRI.…”
Section: Discussionmentioning
confidence: 99%
“…However, suitable time of initiating RRT remains controversial. There is a study showing that serum MMP-10 levels serve as an important predictor of the necessity of emergency RRT in nondiabetic geriatric patients with AKI [62]. Nevertheless, because of the limited number of patients in this study, careful follow-up evaluation with a larger sample size is needed to confirm this finding.…”
Section: Acute Kidney Injurymentioning
confidence: 72%